3(7X+8)=2(2x-4)

Simple and best practice solution for 3(7X+8)=2(2x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(7X+8)=2(2x-4) equation:


Simplifying
3(7X + 8) = 2(2x + -4)

Reorder the terms:
3(8 + 7X) = 2(2x + -4)
(8 * 3 + 7X * 3) = 2(2x + -4)
(24 + 21X) = 2(2x + -4)

Reorder the terms:
24 + 21X = 2(-4 + 2x)
24 + 21X = (-4 * 2 + 2x * 2)
24 + 21X = (-8 + 4x)

Solving
24 + 21X = -8 + 4x

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-24' to each side of the equation.
24 + -24 + 21X = -8 + -24 + 4x

Combine like terms: 24 + -24 = 0
0 + 21X = -8 + -24 + 4x
21X = -8 + -24 + 4x

Combine like terms: -8 + -24 = -32
21X = -32 + 4x

Divide each side by '21'.
X = -1.523809524 + 0.1904761905x

Simplifying
X = -1.523809524 + 0.1904761905x

See similar equations:

| p+3=80 | | -3x+9=6x+81 | | 3(3m-2)=3(m+3) | | 17x-(3x-6)=34 | | 110=10p | | 4a^5*ab= | | 64knots= | | 2x+x+x-6=36 | | (3w-7)(5w-8)=0 | | 432.94=220+0.78x | | -2-3m=-8 | | -8+21=m-1 | | 18x+14y=65 | | 14x^2y-35x=0 | | -6x+3(-4x+23)=-21 | | d-13=25 | | x-9=-1+7 | | -6x+3(-12x+23)=-21 | | 4x+24+3=-35 | | 4m-8=2m+8 | | -6x+10y=26 | | (4x-3)(m+7)=3x | | 0=x^2-6x-16 | | 18v-9v=54 | | .5(8y-2)=16-30y | | 32=-5-3t | | Z^4-9z^2=0 | | 3x+9y+10y+2=180 | | 13-(2x+2)=2(2+x)3x | | 1=2d-1 | | 4(3y-8)-11y=2 | | 5s+3=12 |

Equations solver categories